Rational myths and institutional logics for catholic school analysis: Influences on cultural and behavioral organizational constructing - Velázquez Ugalde, Liliana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The present is a qualitative, ethnomethodological study, where preliminary results of the research carried out in 23 Catholic schools in Mexico are presented, the purpose was to explain, from the approach of the new sociological institutionalism, how myths and institutional logics influence the construction of organizational behavior. Through interviews, field observation, and documentary review, the data were triangulated and constants were identified, both consistency and contradiction between the three levels of social theory: individuals, organizations, and institutions, and the three dimensions of institutional logics: structural, normative and symbolic.